INVESTIGATING THE RELATIONSHIP BETWEEN A SOILS CLASSIFICATION AND THE SPATIAL PARAMETERS OF A CONCEPTUAL CATCHMENT-SCALE HYDROLOGICAL MODEL - Dunn S.M.; Lilly A. (My University, 2001)
There are now many examples of hydrological models that utilise the capabilities of Geographic Information Systems to generate spatially distributed predictions of behaviour. However, the spatial variability of hydrological parameters relating to distributions of soils and vegetation can be hard to establish. In this paper, the relationship between a soil hydrological classification Hydrology of Soil Types (HOST) and the spatial parameters of a conceptual catchment-scale model is investigated. A procedure involving inverse modelling using Monte-Carlo simulations on two catchments is developed to identify relative values for soil related parameters of the DIY model. The relative values determine the internal variability of hydrological processes as a function of the soil type.For three out of the four soil parameters studied, the variability between HOST classes was found to be consistent across two catchments when tested independently. Problems in identifying values for the fourth 'fast response distance' parameter have highlighted a potential limitation with the present structure of the model. The present assumption that this parameter can be related simply to soil type rather than topography appears to be inadequate. With the exclusion of this parameter, calibrated parameter sets from one catchment can be converted into equivalent parameter sets for the alternate catchment on the basis of their HOST distributions, to give a reasonable simulation of flow.Following further testing on different catchments, and modifications to the definition of the fast response distance parameter, the technique provides a methodology whereby it is possible to directly derive spatial soil parameters for new catchments.
Keywords: CATCHMENT-SCALE MODELLING; SPATIALLY DISTRIBUTED SOIL PARAMETERS; SOIL HYDROLOGICAL CLASSIFICATION; CONCEPTUAL MODEL